The integrin antagonist, cilengitide, is a weak inhibitor of αIIbβ3 mediated platelet activation and inhibits platelet adhesion under flow. (February 2015) - Meyer dos Santos, Sascha; Kuczka, Karina; Picard-Willems, Bettina; Nelson, Karen; Klinkhardt, Ute; Harder, Sebastian
Abstract The RGD cyclic pentapetide, cilengitide, is a selective inhibitor of αvβ3 and αvβ5 integrins and was developed for antiangiogenic therapy. Since cilengitide interacts with platelet αIIbβ3 and platelets express αv integrins, the effect of cilengitide on platelet pro-coagulative response and adhesion is of interest. Flow-based adhesion assays were performed to evaluate platelet adhesion and rolling on von Willebrand factor (vWf), on fibrinogen and on human umbilical vein endothelial cells (HUVECs). Flow cytometry was used to detect platelet activation (PAC1) and secretion (CD62P) by cilengitide and light transmission aggregometry was used to detect cilengitide-dependent platelet aggregation. Cilengitide inhibited platelet adhesion to fibrinogen at concentrations above 250 µM [which is the Cmax in human studies] and adhesion to vWf and HUVECs at higher concentrations under physiologic flow conditions. Platelet aggregation was already impaired at cilengitide concentrations >10 µM. Activation of αIIbβ3 integrin was inhibited by 250 µM cilengitide, whereas platelet secretion was unaffected by cilengitide. No evidence of cilengitide-induced platelet activation was found at all tested concentrations (0.01–1500 µM). At higher concentrations, platelet activation was inhibited, predominantly due to αIIbβ3 inhibition.